The Implementation Of Islamic Multicultural Learningvalue Through Aswaja And Nu: (Case study at MI Miftahul Huda Papungan 01 Blitar) - arif muzayin shofwan (Journal of Development Research, 2017)
Many ways to implement Islamic multicultural learningvalue in the school or madrasah, one of them through Aswaja and NU. The purpose of this study is observingthe implementation of Islamic multi-cultural value through Aswaja and NU at MI Miftahul Huda Papungan 01, Sekardangan, Kanigoro, Blitar, JawaTimur. The implementation of Islamic multicultural education value be able to make the students be multiculturalist human that can respect all of differences. The result of implementation of Islamic multicultural learning value through Aswaja and NU at MI Miftahul Huda Papungan 01 is success because of significant to the opinion of multicultural expert based on some criteria as follows: First, improving students‟ skill by having ability to know, to accept, to respect, and to celebrate multi-cultural. Second, instructing and emphasizing the learning in the democratic life. Third, teaching and emphasizing the learningthat headed forjustice, freedom and racism, sarcasm, social domination and other intolerances.